Annotated bird sighting list for Fall 1983 compiled by Babs Padelford - Padelford, Babset al (1983)
An annotated list of birds sighted by Babs Padelford. Includes letter explaining possible Tundra Swan sighting. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1983. Epson - sheet feed/flatbed